Assessment of nutritional status of primary school children by anthropometry in rural field practice area of Father Muller Medical College, Mangalore - Aramani, Anita; Kumar, Saurabh; Prabhu, Sudhir; Acharya, Das (International Journal Of Community Medicine And Public Health, 2019)
Background: Malnutrition in the primary school children is one of important problems in India with long term ramifications. This may be related to faulty dietary habits, socioeconomic condition of the family etc. Malnutrition especially undernourishment can lead to delay in growth and development. Anthropometric assessment of the school children provides the information regarding the nutritional status. The objectives of the study were to find out the prevalence of undernourishment, overweight and obesity in the primary school children of the rural field practice area; to find out the association of socio-demographic variables with nutritional status. Methods: Cross sectional study was conducted from November 2013- February 2014 to assess the nutritional status of the primary school children of the rural field practice areas of our institution in Thumbay region of Dakshina Kannada. Results: The prevalence of undernourishment (thinness and severe thinness) and overweight and obesity was found to be 40.5%, 2.8% and 1.3% respectively. It was also found that significantly higher proportion of male students was having severe thinness compared to females. Conclusions: The present study showed that undernourishment (thinness) was still a problem in the rural area school children.